2014
DOI: 10.1007/s00259-014-2850-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the prognostic values of 68Ga-DOTANOC PET/CT and 18F-FDG PET/CT in patients with well-differentiated neuroendocrine tumor

Abstract: SUVmax measured on (68)Ga-DOTANOC PET/CT is an independent, positive prognostic factor in patients with well-differentiated NET and is superior to SUVmax on (18)F-FDG PET/CT and conventional clinicopathological factors for predicting PFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 24 publications
1
45
2
Order By: Relevance
“…Interestingly, there was no relation between FDG SUV max and grade. The only report with similar findings was by Sharma et al in a limited population of NET patients with different primary sites (36). In their study, SUV max for 68 Ga-DOTANOC correlated with prognosis, whereas that for 18 F-FDG did not.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Interestingly, there was no relation between FDG SUV max and grade. The only report with similar findings was by Sharma et al in a limited population of NET patients with different primary sites (36). In their study, SUV max for 68 Ga-DOTANOC correlated with prognosis, whereas that for 18 F-FDG did not.…”
Section: Discussionsupporting
confidence: 61%
“…Recent papers have investigated the value of 68 Ga-DOTANOC SUV max as a potential prognostic factor (35)(36)(37). We used a cutoff of 5% when relating Ki-67 to SUV max based on the study of Panzuto et al reporting that patients with a Ki-67 of more than 5% show more aggressive disease (37).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, regarding the correlation between the 68 Ga-DOTATATE PET/CT results and patient survival, our study revealed statistically significant differences (P 5 0.000) in 1-, 3-, and 5-y survival, as expected, between patients with true-negative and true-positive scans. There are small published reports regarding the prognostic value of the SUV max on 68 Ga-DOTA-peptide PET scanning in patients with NETs (21,22) and the change in tumor-to-spleen SUV ratio as an independent predictor of progression-free survival after PRRT (23). In our study, we did not attempt to correlate the SUV, as a semiquantitative marker of SSTR expression, with survival, as it is part of a separate study.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have investigated the role of grading, staging, functioning status, and somatostatin receptor density as potential prognostic factors in pNETs (8). Two studies indicated that SUV max measured in the lesion with the highest 68 Ga-DOTANOC uptake was a prognostic parameter in heterogeneous populations of neuroendocrine tumors with different primary sites (including gastroenteropancreatic and lung tumors) (9,10).…”
mentioning
confidence: 99%